Yield-line mechanisms and design proposal for endplate connections in rectangular hollow section members in tension. (15th March 2023) - Timmers, R.; Lang, R.
Highlights: Previously unknown failure mechanisms were discovered with the DLO method. A Eurocode EN 1993–1-8 conform design proposal was developed. The new design proposal covers a wide range of practical connection layouts. Abstract: Hollow section members are popular elements in steel constructions, especially when they are mainly loaded by normal forces, like simply supported columns or truss members. The individual hollow section members can be combined by bolted endplate connections. If the bolts are arranged at all four sides of the rectangular hollow section, the design rules for the T -stub model from the widely used Eurocode EN 1993–1-8 cannot be applied due to the missing failure mechanisms (yield-line mechanisms) of the whole plate. The presented research deals with this problem. A parameter study on different endplate layouts with and without chamfers has been done using a verified numerical model. The numerical model is based on the discontinuity layout optimization (DLO) method and delivers all the relevant yield-line mechanisms of the plate and bolts. Based on these observed failure mechanisms, a simple and Eurocode conform design proposal has been worked out for endplates with and without chamfers. The obtained resistances from the design proposal and the DLO calculations are within a deviation of approximately 10%.